Communication Strategies to Improve Child Participation in Triadic Consultations Within Healthcare Settings: A Scoping Review - Maha Alharbi; Suzanne Grant; George Cherukara; Siyang Yuan (Health Expectations, 2026)
ABSTRACT Introduction Children under 18 are recognised as key stakeholders in healthcare and possess the right to actively participate in decisions regarding their care. Despite this, they are frequently relegated to passive roles during triadic healthcare consultations involving healthcare providers (HCPs), caregivers, and children. Enhancing child participation requires effective communication strategies; however, numerous barriers persist, including healthcare provider dominance and parental interference. This review aims to explore and identify effective communication strategies employed by healthcare providers and caregivers to improve child participation in triadic consultations within healthcare settings. Method A scoping review methodology, based on the Joanna Briggs Institute framework and PRISMA guidelines, was used. A comprehensive search was conducted across four databases—PubMed, PsycINFO, Scopus, and CINAHL using predefined eligibility criteria. Studies focused on children under 18 in triadic healthcare consultations. Qualitative, quantitative, and mixed‐methods studies were included to map existing evidence and highlight gaps. Results A total of 37 out of 41 studies revealed that child participation in triadic consultations is frequently minimal and varies significantly depending on the communication styles of HCPs and caregivers. HCPs exhibit a range of communication styles, with some adopting a directive or task‐focused (Dyadic approach) that prioritises medical tasks and often sidelines children in conversations, while others utilise supportive and facilitative styles (Triadic approach) that emphasise rapport‐building, open‐ended questioning, child‐friendly language, and the use of interactive techniques that facilitate engagement. Parental roles in this dynamic were classified into three main styles: supportive facilitator, dominant and protective. Factors such as the child's age and developmental stage, wider cultural influences, the emotional context, and the healthcare environment were also found to significantly impact child participation. A variety of measurement tools were utilised to assess participation levels, including the Roter Interaction Analysis System (RIAS), conversational analysis and context‐specific coding schemes. However, the review identified a notable lack of standardised tools, which limits the comparability of findings across different studies. Conclusion This review highlights the need to enhance child participation in healthcare consultations through effective communication. However, improving participation requires more than communication skills training alone. HCPs must work closely alongside parents and caregivers to support children's participation rights and embed these principles in routine practice. Achieving this objective requires engaging both HCPs and parents to drive changes in clinical practice through a fundamental cultural shift in paediatric care delivery. Future research should employ validated measurement tools to evaluate progress and identify effective approaches to enhancing child engagement in healthcare settings. Patient and Public Contribution The findings have been discussed with Patient and Public Involvement (PPI) members who have children. Their valuable insights contributed to the interpretation of the review findings and informed the next stage of the project, which will include audio observation of triadic consultations in paediatric dental settings.